Methods and tools for diagnosing bridge structures - Філоненко, С.Ф.; Корнієнко, І.К.; Косицька, Т.М. (Proceedings of National Aviation University, 2008)
In the paper is reviewed the methods and means, which used at technical diagnostic of bridge designs. The general approaches to technical diagnostic, the main methods, primary converters and hardwares, which used on static and dynamic tests of bridge designs are reviewed.